BMAL1 moonlighting as a gatekeeper for LINE1 repression and cellular senescence in primates. Issue 6 (14th March 2022) - Liang, Chuqian; Ke, Qiong; Liu, Zunpeng; Ren, Jie; Zhang, Weiqi; Hu, Jianli; Wang, Zehua; Chen, Hong; Xia, Kai; Lai, Xingqiang; Wang, Qiaoran; Yang, Kuan; et al.
Abstract: Aging in humans is intricately linked with alterations in circadian rhythms concomitant with physiological decline and stem cell exhaustion. However, whether the circadian machinery directly regulates stem cell aging, especially in primates, remains poorly understood. In this study, we found that deficiency of BMAL1, the only non-redundant circadian clock component, results in an accelerated aging phenotype in both human and cynomolgus monkey mesenchymal progenitor cells (MPCs). Unexpectedly, this phenotype was mainly attributed to a transcription-independent role of BMAL1 in stabilizing heterochromatin and thus preventing activation of the LINE1-cGAS-STING pathway. In senescent primate MPCs, we observed decreased capacity of BMAL1 to bind to LINE1 and synergistic activation of LINE1 expression. Likewise, in the skin and muscle tissues from the BMAL1-deficient cynomolgus monkey, we observed destabilized heterochromatin and aberrant LINE1 transcription. Altogether, these findings uncovered a noncanonical role of BMAL1 in stabilizing heterochromatin to inactivate LINE1 that drives aging in primate cells.